A new strategy based on hybrid battery–wind power system for wind power dispatching. Issue 1 (12th October 2017) - Gholami, Mehrdad; Fathi, Seyed Hamid; Milimonfared, Jafar; Chen, Zhe; Deng, Fujin
Abstract : Battery energy storage system (BESS) is one of the best solutions to compensate the wind power fluctuations and forecasting errors for participation in the power markets by contribution in the energy production several hours ahead. Based on coordination of BESS and wind power, this study aims to present a new strategy to optimise the BESS size and increase the battery lifetime. In the proposed strategy, the average wind power is considered as the dispatch power to minimise the battery capacity and two back up battery sets are utilised to avoid shallow charge–discharge cycles for saving the battery efficiency and lifetime. In addition, the short‐term operation criterion is chosen to deal with the prediction error effects. The proposed method is applied to a 2 MW wind turbine as a case study with 2 years wind data. Simulation results show the effectiveness of the proposed strategy.